Conference in German Lithuanian culture centre - Brandišauskas, Valentinas (Genocidas ir rezistencija, 2002)
On 28–30 September 2001, the 21st convention – scientific conference of the Lithuanian Cultural Institute (LCI) was held at the German Lithuanian Cultural Centre in Hüttenfeld. This time the conference was thematic and focused on the events of the Second World War.